Zrównoważona mobilność w miastach – wyzwania i perspektywy - Wójcik, Szymon (Public participation in urban climate policy making: The example of Lodz, 2024)
This chapter aims to discuss perspectives for shaping urban mobility in the context of climate change and to identify solutions that reduce urban emissions in the transportation sector. The environmentally harmful externalities generated by motorized transport, as revealed by current scientific research, are discussed. Subsequently, the developmental status of selected Polish cities’ sustainable transport solutions is characterized. Data analysis indicates upward trends in expanding dedicated bus lanes, developing public bicycle road networks, constructing Park & Ride facilities, and increasing popularity of electric scooters. These positive trends are contrasted with a consistent increase in motorization ratios within the analyzed cities, posing a challenge for emissions reduction within their boundaries. The chapter concludes with recommendations for urban transport policies that promote sustainable mobility.